Image analysis based validation and kinetic parameter estimation of rice cooking - Amogha, V.; Shinde, Yogesh; Pandit, A.; Joshi, J. (2017)
© 2017 Wiley Periodicals, Inc. The thermal efficiency of currently employed cooking methods ranges between 10 and 25%. Cooking accounts for ~40% of total energy consumed in developing world indicating toward huge scope for improvement. To develop the cooking methods of better efficiency, bringing down the energy consumption, it is necessary to understand the kinetics of cooking. As rice is a staple food for nearly 50% of the world's population, an attempt is made to scientifically explore the kinetics of rice cooking process. It is a well-known fact that presoaking of the rice reduces the cooking time and thus reduces energy consumption, to support this numerically, different parametric measurements such as moisture absorption, change in dimensions (length and width) of rice grain while cooking, are utilized for estimating the cooking kinetics. In addition, the technique of image analysis was also used for easy and quick estimation of the extent of cooking. Experiments were performed with both un-soaked and presoaked rice at three different temperatures (80, 90, and 97 °C) to evaluate the kinetics of rice cooking process. The activation energies for cooking of un-soaked and presoaked rice were found to be ~ 75 kJ/mol and ~ 70 kJ/mol, respectively, which is in good agreement with the values reported in literature. Regime of operation for cooking of rice is found to be diffusion controlled based on swelling particle model. Practical applications: Around 40 % of the total energy consumed in the developing world (population more than 496 billion) goes in cooking processes (Joshi et al.,). This huge energy consumption can be attributed to the inefficiencies related to cooking methods and/or devices. There is an urgent need to employ an energy efficient engineering solution for preparing hygienic, nutritious meals, which also has advantages of energy efficiency, ease of operation and efficient resource utilization. In order to design any efficient cooking device, kinetics of cooking for particular food material must be studied. Shinde et al. (), Joshi et al. () have designed the energy efficient batch and continuous cookers. Presented work utilizes simple method for determining kinetics of rice cooking, which can be easily extended to obtain kinetics of any other food material.